Improving Problem-Solving Skills With Problem-Based Learning Models in Optical Wave Courses - Mirza Roma Apsari; Zainul Arifin Imam Supardi; Rinie Pratiwi Puspitawati; Mohammad Budiyanto (Indonesia Emerging Literacy Education, 2023)
Objective: Problem-solving skills are one of the skills one has to live in the 21st century. Therefore, this research aims to explain the improvement in problem-solving skills using a problem-based learning model in optical wave courses. This research was carried out on 3rd-semester students majoring in undergraduate program Science Education at the State University of Surabaya in two classes. Method: The research design used the one-group pretest-posttest design with one repetition—data collection techniques using observation and test techniques. Observations were made to review practical aspects and tests for reviewing the effectiveness aspects. Results: The observation results indicate that the learning process is classified as practical. The average result of problem-solving skills in class U students is better than in class B. Based on their problem-solving skills, students can solve problems to completion. The knowledge test results are in the moderate range. A paired T-test in each class shows a significant difference between the results before and after learning. The achievement of knowledge and skills shows that the problem-based learning model effectively improves their problem-solving skills in the waves and optics courses. Novelty: The novelty of this research is the use of four indicators adapted to optical wave material under learning conditions after the COVID-19 pandemic.